Lactobacillus-Depleted Vaginal Microbiota in Pregnant Women Living With HIV-1 Infection Are Associated With Increased Local Inflammation and Preterm Birth - Short, Charlotte-Eve S.; Brown, Richard G.; Quinlan, Rachael; Lee, Yun S.; Smith, Ann; Marchesi, Julian R.; Shattock, Robin; Bennett, Phillip R.; Taylor, Graham P.; MacIntyre, David A. (Frontiers in Cellular and Infection Microbiology, 2021)
Background Pregnant women living with HIV-1 infection (PWLWH) have an elevated risk of preterm birth (PTB) of unknown aetiology, which remains after successful suppression of HIV. Women at high risk for HIV have a common bacterial profile which has been associated with poor birth outcomes. We set out to explore factors associated with gestational age at delivery of PWLWH in a UK population. Methods Prospective study of PWLWH (n = 53) in whom the vaginal microbiota and cervicovaginal cytokine milieu were assessed using metataxonomics and multiplexed immunoassays, respectively. Cross-sectional characterisation of vaginal microbiota in PWLWH were compared with 22 HIV uninfected pregnant women (HUPW) at a similar second trimester timepoint. Within PWLWH the relationships between bacterial composition, inflammatory response, and gestational age at delivery were explored. Findings There was a high rate of PTB among PWLWH (12%). In the second trimester the vaginal microbiota was more diverse in PWLWH than in HUPW (Inverse Simpson Index, p = 0.0004 and Species Observed, p = 0.009). PWLWH had a lower prevalence of L. crispatus dominant vaginal microbiota group (VMB I, 15 vs 54%) than HUPW and higher prevalence of L. iners dominant (VMB III, 36 vs 9% and VMB IIIB, 15 vs 5%) and mixed anaerobes (VMB IV, 21 vs 0%). Across the second and third trimesters in PWLWH, VMB III/IIIB and IV were associated with PTB and with increased local inflammation [cervicovaginal fluid (CVF) cytokine concentrations in upper quartile]. High bacterial diversity and anaerobic bacterial abundance were also associated with CVF pro-inflammatory cytokines, most notably IL-1β. Interpretation There is an association between local inflammation, vaginal dysbiosis and PTB in PWLWH. Understanding the potential of antiretroviral therapies to influence this cascade will be important to improve birth outcomes in this population.